Social Support: From Exclusion Criteria to Medical Service - Appel, Jacob M. (Cambridge quarterly of healthcare ethics, 2024)
One of the criteria used by many transplant centers in assessing psychosocial eligibility for solid organ transplantation is social support. Yet, social support is a highly controversial requirement that has generated ongoing debate between ethicists and clinicians who favor its consideration (i.e., utility maximizers) and those who object to its use on equity grounds (i.e., equity maximizers). The assumption underlying both of these approaches is that social support is not a commodity that can be purchased in the marketplace. This essay argues for the reconceptualization of social support as a product that can—and should—be purchased for transplant candidates to render them eligible for transplant.